Effect of self-esteem in the relationship between stress and substance abuse among adolescents: A mediation outcome - Ikechukwu, Uba; Siti, Nor Yaacob; Mansor Abu Talib,; Mofrad, Sakineh *; Rohani Abdullah, (IACSIT Press, 2013)
The present study assessed the mediating effect of self-esteem in the relationship between stress and substance abuse among adolescents. The participants of the study were 352 adolescents, 54.5% males and 45.5% females aged 13 to18 years, from selected secondary schools in Somolu, Lagos, Nigeria. Substance abuse was measured with the Drug Abuse Screening Test, while stress was measured with the Perceived Stress Scale, and Self-esteem was measured with the Rosenberg Self-esteem scale. The study ascertained a negative and large correlation (r = -.538, p <.01) between stress and self-esteem, similar results (r = -.536, p <.01) was found between self-esteem and substance abuse and a positive and medium correlation (r = .360, p <.01) was found between stress and substance abuse. Self-esteem partially mediated the relationship between stress and substance abuse. Recommendations of the study highlighted the need for greater enlightenment on the importance of self-esteem particularly among adolescents